Pupylated proteins in Corynebacterium glutamicum revealed by MudPIT analysis. Issue 12 (16th May 2014) - Küberl, Andreas; Fränzel, Benjamin; Eggeling, Lothar; Polen, Tino; Wolters, Dirk Andreas; Bott, Michael
<x xml:space="preserve">Abstract</x> In a manner similar to ubiquitin, the prokaryotic ubiquitin‐like protein (Pup) has been shown to target proteins for degradation via the proteasome in mycobacteria. However, not all actinobacteria possessing the Pup protein also contain a proteasome. In this study, we set out to study pupylation in the proteasome‐lacking non‐pathogenic model organism Corynebacterium glutamicum. A defined pup deletion mutant of C. glutamicum ATCC 13032 grew aerobically as the parent strain in standard glucose minimal medium, indicating that pupylation is dispensable under these conditions. After expression of a Pup derivative carrying an aminoterminal polyhistidine tag in the Δpup mutant and Ni2+‐chelate affinity chromatography, pupylated proteins were isolated. Multidimensional protein identification technology (MudPIT) and MALDI‐TOF‐MS/MS of the elution fraction unraveled 55 proteins being pupylated in C. glutamicum and 66 pupylation sites. Similar to mycobacteria, the majority of pupylated proteins are involved in metabolism or translation. Our results define the first pupylome of an actinobacterial species lacking a proteasome, confirming that other fates besides proteasomal degradation are possible for pupylated proteins.